Implementasi Kegiatan Mentoring dalam Pembinaan Karakter Religius Siswa di SMP Swasta An Nizam Medan - Feri Azlina; Nurmawati Nurmawati (Jurnal Ilmiah Global Education, 2026)
The cultivation of religious character in schools is often hindered by rigid theoretical classroom approaches, necessitating an adaptive, contextual model. This study aims to analyze the planning, implementation, and evaluation of mentoring activities in developing students' religious character at SMP Swasta An Nizam Medan. This research employs a qualitative-descriptive approach, gathering data through participant observation and in-depth interviews with Islamic Education teachers, mentors, and students. The findings indicate that mentoring planning is conducted systematically and collaboratively, focusing on nurturing faith (aqidah), worship (ibadah), and morals (akhlak) through varied methods and worship control books. The evaluation proves that the program yields a significant positive impact, strongly supported by the synergy of the principal, teachers, parents, and a structured monitoring system. The managerial implication highlights that character building requires an integrated oversight ecosystem rather than mere knowledge transfer. However, the primary limitation lies in its localized qualitative scope, with evaluations identifying constraints such as limited duration and varying student participation. Therefore, future research is recommended to utilize a mixed-methods design across multiple schools to assess the long-term effectiveness of mentoring programs on retaining students' religious behavior in the digital era.